2020
DOI: 10.5603/dk.2019.0026
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between biomarkers of oxidative stress, glycemic control and insulin resistance in women with type 2 diabetes

Abstract: Background. The main characteristic of type 2 diabetes mellitus (T2DM) is hyperglycemia due to insulin resistance. Enhanced oxidative stress owing to increased oxygen free radicals and/or reduced antioxidant defense has very important roles in T2DM development and also most of its complications. The aim of the current study was to evaluate correlations between biomarkers of oxidative stress, glycemic control and insulin resistance in women with T2DM. Materials and methods. Seventy nine women with T2DM were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Picu et al [27] has shown a positive correlation between total oxidant status and HbA1c. Khosrowbeygi et al [28] observed significant negative correlation between values of HbA1c and total antioxidant capacity. This highlights that oxidative stress is a potential covariate in predicting patient response to antidiabetic treatment, and GSTP1 genotyping can be relevant for better identification of T2D patients who are likely to need specific pharmacological strategies focusing not only on lowering glucose [29], but also on oxidative stress.…”
Section: Discussionmentioning
confidence: 97%
“…Picu et al [27] has shown a positive correlation between total oxidant status and HbA1c. Khosrowbeygi et al [28] observed significant negative correlation between values of HbA1c and total antioxidant capacity. This highlights that oxidative stress is a potential covariate in predicting patient response to antidiabetic treatment, and GSTP1 genotyping can be relevant for better identification of T2D patients who are likely to need specific pharmacological strategies focusing not only on lowering glucose [29], but also on oxidative stress.…”
Section: Discussionmentioning
confidence: 97%
“…Studies show that individuals with T2DM experience increased oxidative stress due to elevated reactive oxygen species activity and/or decreased antioxidant defence mechanisms. Chronic high blood glucose levels induce oxidative stress, leading to impaired pancreatic β cell functioning, exacerbating insulin resistance, and promoting vascular complications [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, oxidative stress is considered one of the most important pathological factors in the progression of metabolic diseases [6,9,10,15,16]. Therefore, it is not surprising that redox biomarkers have been postulated for the diagnosis of IR [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%